Mapping Global Research on Cyber Bullying in the Context of Cross-Cultural Collaborations: A Bibliometric and Network Analysis - Peker, Adem; Yalçın, Ragıp Ümit (Frontiers in Communication, 2022)
The increasing prevalence of communication tools also increases the negative use of the individual, which will disrupt communication with others. One consequence of this negative use is defined as cyber bullying and it can negatively affect the mental health of individuals. This study adopts a descriptive bibliometric approach to map global research on cyber bullying using metadata from the Web of Science database. Analysis of publication trends at the country level shows that cyber bullying and cross-cultural research is a growing research area in recent years. In addition, researchers conduct studies on cyberbullying and intercultural cooperation in different parts of the world. Co-authoring network analyzes revealed that we conducted the most effective research on cyber bullying in the USA, and collaborations on cyber bullying research were heterogeneous, except for some regions. The visual network map shows that there is cooperation between authors and institutions in studies on cyber bullying. All the top 5 universities that make the most publications on cyber bullying are within the member states of the European Union